2016
DOI: 10.1128/mbio.00465-16
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of a Yci1 Domain Protein of Candida albicans Allows Homothallic Mating in MTL Heterozygous Cells

Abstract: It has been proposed that the ancestral fungus was mating competent and homothallic. However, many mating-competent fungi were initially classified as asexual because their mating capacity was hidden behind layers of regulation. For efficient in vitro mating, the essentially obligate diploid ascomycete pathogen Candida albicans has to change its mating type locus from heterozygous MTLa/α to homozygous MTLa/a or MTLα/α and then undergo an environmentally controlled epigenetic switch to the mating-competent opaq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 47 publications
(65 reference statements)
1
12
0
Order By: Relevance
“…In clusters 0 and 2, WH11 and STF2 were significantly downregulated compared with cluster 1 (Figure 4D). Genes involved in fermentation, such as ADH1, were upregulated in cluster 0, consistent with previous studies of opaque cells 22 .…”
supporting
confidence: 90%
“…In clusters 0 and 2, WH11 and STF2 were significantly downregulated compared with cluster 1 (Figure 4D). Genes involved in fermentation, such as ADH1, were upregulated in cluster 0, consistent with previous studies of opaque cells 22 .…”
supporting
confidence: 90%
“…RNA-seq libraries were constructed using Illumina's miSEQ RNA Sample Preparation Kit (Illumina Inc., USA). RNA sequencing, data analysis and sequence assembly were performed by the Quebec Genome Innovation Center at McGill University (Montreal, Canada) [31,38]. Preparation of the paired-end libraries and sequencing were performed following standard Illumina methods and protocols.…”
Section: Rna Sequencing and Data Analysismentioning
confidence: 99%
“…Inactivation of the Bar1 protease or the Dipeptidyl aminopeptidase YC1 (Yci1) domain protein Opaque Formation Regulator 1 (Ofr1) has been shown to induce same-sex mating in C . albicans [ 16 , 44 ]. We observed that BAR1 was not down-regulated but rather highly induced upon glucose starvation ( Fig 1 ).…”
Section: Discussionmentioning
confidence: 99%